Vegetation Dynamics and Megaherbivore Presence of MIS 3 Stadials and Interstadials 10–8 Obtained from a Sediment Core from Auel Infilled Maar, Eifel, Germany - Sarah Britzius; Frank Sirocko (Quaternary, 2023)
We present a record of pollen and spores of coprophilous fungi from a sediment core from Auel infilled maar, Eifel, Germany, covering the period from 42,000 to 36,000 yr b2k. We can show that vegetation cover was dominated by a boreal forest with components of steppe and cold-temperate wood taxa. The proportion of wood taxa was higher during interstadials, whereas steppe-vegetation became more prominent during stadials. During Heinrich stadial 4, temperate taxa are mostly absent. Spores of coprophilous fungi show that megaherbivores were continuously present, albeit in a larger number during stadials when steppe environment with abundant steppe herbs expanded. With the onset of Greenland stadial 9, forests became more open, allowing for steppe-environment to evolve. The shift in vegetation cover coincides with the highest values of herbivore biomass at the time that Neanderthal humans demised and Anatomically Modern Humans most probably arrived in Central and Western Europe. Megaherbivore biomass was a direct consequence of vegetation cover/availability of food resources and thus an indirect consequence of a changing climate. Herds of large herbivores following suitable (steppe) habitats may have been one cause of the migration of AMH into Europe, going along with their prey to productive hunting grounds.